Efektivitas Parsons Problem 2D terhadap Pemahaman Logika dan Struktur Kontrol pada Pembelajaran Pemrograman Berorientasi Objek - Eka Larasati Amalia; Dimas Wahyu Wibowo; Muhamad Saifulloh Bahroin Gana; Retno Damayanti (Universitas PGRI Kanjuruhan Malang, 2026)
Students’ understanding of logic and control structures in object-oriented programming remains a major challenge in programming education. Based on a survey conducted by the researcher involving 30 third-semester students of the Informatics Engineering Study Program from the 2024 cohort, 69,7% of students stated that they experienced difficulties in understanding OOP materials. These difficulties are generally caused by the complexity of syntax and students’ limited focus on program logic flow. Therefore, appropriate learning media are needed to help students understand programming concepts in a more structured manner. This study aims to evaluate the effectiveness of the 2D Parsons Problem feature in improving students’ understanding of logic and control structures in object-oriented programming. This study employed a quantitative approach using a one-group pretest–posttest design. The research participants consisted of 42 students who had completed the Object-Oriented Programming course. Data were collected through pretests and posttests and analyzed using the Normalized Gain (N-Gain) method to measure improvements in students’ understanding. The results showed an increase in the average score from 57,9 in the pretest to 89,5 in the posttest, with an average N-Gain value of 0.715, which falls into the high improvement category. A total of 28 students were categorized as having high improvement, 12 as moderate improvement, and 2 as low improvement. These findings indicate that the 2D Parsons Problem feature is effective in enhancing students’ understanding of logic and control structures in object-oriented programming.